PERAN SOCIAL MATURITY DALAM MEMBANGUN SCHOOL READINESS PADA MURID PRASEKOLAH KAYATA SCHOOL BERASTAGI - Yulinda Septiani Manurung; Winida Marpaung (Universitas HKBP Nommensen, 2019)
This study aims to see how the readiness of preschool children to enter primary school, especially their social maturity. The subjects of the study were 15 Berastagi Kayata School preschoolers aged four to seven year old. Data was taken with the Nijmeegse Schoolbekwaamheidstest (NST) test to obtain a picture of children's school readiness and the Vineland Adaptive Behavior Scale (VABS) to look more specifically at a child's social maturity. The research data were analyzed descriptively with a quantitative approach. The results obtained in this study are as the chronological age of Kayata School preschoolers become more mature, they are intellectually ready to enter elementary school. But socially and emotionally, their readiness is still not optimal to be able to participate in learning activities in elementary schools.